HUBUNGAN PLATELET-LYMPHOCYTE RATIO DENGAN KEJADIAN SINDROM KORONER AKUT UNSTABLE ANGINA DI RSPAL DR. RAMELAN SURABAYA - Dewi, Ratna Chintya (Fakultas Kedokteran, Universitas Hang Tuah, 2025)
Background: Coronary Heart Disease (CHD) is a cardiovascular disease that causes the most deadly in the world with manifestations in the form of Acute Coronary Syndrome (ACS). One of the ACS categories is unstable angina. Platelet-Lymphocyte Ratio (PLR) are two combinations of hematological parameters that have recently emerged as predictors of various cardiovascular diseases. Objective: To determine the relationship between PLR and the incidence of Acute Coronary Syndrome unstable angina at RSPAL dr. Ramelan Surabaya. Method: This study is a cross-sectional retrospective using medical records of patients with ACS in the cardiology department's outpatient and inpatient installations RSPAL dr. Ramelan Surabaya. Results: The number of medical record data that met the inclusion criteria was 181 samples. 64% of patients are male and 36% are female. Research subjects with PLR ≥109.5 were 60% and PLR <109.5 were 40%. Patients with unstable angina are 66% and not unstable angina is 34%. The results of the data analysis test using the contingency coefficient test with cross-tabulation obtained a value of 0.009 with a significance value of 0.899 (P > α). The statistical test results showed that there was no correlation between the platelet-lymphocyte ratio and the incidence of unstable angina at RSPAL dr. Ramelan Surabaya. Conclusion: There is no relationship between platelet-lymphocyte ratio and the incidence of unstable angina at RSPAL dr. Ramelan Surabaya.